AN ANALYSIS OF CODES USED BY THE MOSLEM SPEECH COMMUNITY OF TELAGAMAS VILLAGE, SUBAGAN, KARANGASEM - ., Andriyani; Putra I.N.A.J, A.; W, Swandana (Jurnal Pendidikan Bahasa Inggris undiksha, 2018)
ABSTRACTThis qualitative research aimed at identifying kinds of code that are used by Moslem people in Telagamas Village and analyzing how they used those codes to communicate with each other and other people around this village. There were three domains chosen in this study, namely family, friendship, and neighborhood. The data were collected using two techniques, namely observation, and interview technique. There were three conversations recorded in all domains of language used and the data were analyzed using observation sheet in a form of table. The results of the study show that there were 3 kinds of code used by the Moslem people in Telagamas Village based on 610 utterances that had been analyzed, namely Sasak language, Balinese, and Indonesian. In addition, there were 46 utterances categorized as code switching and code mixing used by the villagers. There were 32 utterances (70%) that belonged to code switching and 14 utterances (30%) to code mixing.Â Keywords: Code, Code Switching, Code Mixing